Difusi Inovasi Dakwah Digital pada Komunitas @Remisyaofficial di Instagram dalam Mempersuasi Program Dakwah di Kalangan Remaja - Saidah, Musfiah; Irmayanti, Ade (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2024)
The development of communication and information technology in this digital era has influenced various aspects of human life, especially in obtaining information. Various telecommunications innovations are increasing, especially as internet access and social media are available. One of the social media platforms that is popular among Indonesian people, especially the younger generation and teenagers, is Instagram. Instagram makes it easy for its users to interact with each other and share information, including da'wah information. As is done by the Remisya community, which uses Instagram as a means to spread da'wah information. Therefore, this research aims to analyze the process of diffusion of digital da'wah innovations in the Remisya community in persuading teenagers on Instagram. This research uses qualitative methods with a phenomenological approach and a constructivist paradigm. Meanwhile, this research data was obtained through observation, in-depth interviews and documentation. Meanwhile, the diffusion of innovation theory introduced by Everett M. Rogers is used as an analytical tool to understand how Instagram was adopted by the Remisya community in spreading da'wah information. The results of this research show that the process of diffusion of digital da'wah innovation in the Remisya community is able to persuade teenagers to take part in their da'wah program. By paying attention to several elements of innovation diffusion and the innovation decision-making process which involves several stages, including the ability of the Remisya community to adopt and adapt to digital technology for da'wah purposes.